Cross‐cultural assessment of the impact of eczema in six countries with different lifestyles. (1st November 2022) - Merhand, Stéphanie; Taieb, Charles
Abstract: Atopic dermatitis or eczema is a common skin disease in children but also in adults; in Europe alone, it affects more than 23 million adults. At the time of internationalization of studies, it seems important to know that the impact of eczema is different according to lifestyle. It seems that the use of two patient‐reported outcomes, one specific, the other not, to measure the impact of eczema is relevant and should be recommended.